Symbian OS S60 platform implementation of a smartphone-based automatic speech recognition system for the Filipino speech corpus - Ang, Federico M. (2007)
In this project, a speaker-independent Filipino Speech-to-Text (STT) system was realized on a smartphone complemented by a PC. The system is composed of a front-end application that was built to run in Nokia 3rd edition smartphones and a Linux-based decoder from ICSI that was ported to run on a desktop PC running Windows OS. Transfer of files between the mobile device and the desktop computer is done via Bluetooth. The front-end application covers significant portions of a standard speech recognition system, namely, capture of speech input, feature extraction, and estimation of posterior probabilities. The tools from SPRACHcore, a full source code release of speech recognition tools from ICSI, were used to model the algorithms used by the system. Feature extraction used PLP-RASTA features directly converted to cepstral values. Posterior probability estimation was made possible with the use of a multi-layer perceptron. Necessary training and language modelling was done to produce the acoustic and language models. The UP DSP Lab Filipino Speech Corpus (FSC), a database of system performance had an average word recognition rate of 53.94% for isolated word recognition in a moderately noisy environment. For phrase and sentence recognition, the average recognition rate was 6.15%.